2016
DOI: 10.1002/jbm.b.33703
|View full text |Cite
|
Sign up to set email alerts
|

Radiological, histological, and hematological evaluation of hydroxyapatite‐coated resorbable magnesium alloy screws placed in rabbit tibia

Abstract: Titanium (Ti) screw has excellent mechanical property, and osseointegration capacity. However, they require surgery for removal. In contrast, polymer screws are resorbable, but they have poor mechanical properties. In this research, magnesium alloy screws (WE43: Mg-Y-Nd-Zr) that have advantages of titanium and polymer were manufactured. In addition, to increase biocompatibility and control degradation rate, the Mg alloy was coated with hydroxyapatite (HA). Torsion test and corrosion test were performed in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Lim et al [ 15 ], in 2016, reported that the blood magnesium level was found to be within the normal range when WE43 Mg alloy was inserted on the tibia of rabbits. Zhang et al [ 16 ] ran blood tests after inserting a Mg-Zn-Mn alloy on the femur of rats, and the result showed elevated BUN, serum creatinine, AST, and ALT above the norm.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al [ 15 ], in 2016, reported that the blood magnesium level was found to be within the normal range when WE43 Mg alloy was inserted on the tibia of rabbits. Zhang et al [ 16 ] ran blood tests after inserting a Mg-Zn-Mn alloy on the femur of rats, and the result showed elevated BUN, serum creatinine, AST, and ALT above the norm.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 53 reported that blood tests like BUN, serum creatinine, AST, and ALT were elevated than the normal limit after inserting an Mg‐Zn‐Mn alloy in the femur of rats. The normal range of blood magnesium level was found by Lim et al 54 in the study when Mg alloy was inserted in the tibia of rabbits.…”
Section: Discussionmentioning
confidence: 61%
“…be biocompatible with no toxicity as revealed by hema tological test following placement of HA-WE43 screws in rabbit's tibia[4]. The present study' s use of HA-WE43 indicated its benefit in providing a well-controlled degraded conduit without any observable accumulated gas.…”
mentioning
confidence: 52%
“…The WE43 fabrication and HA coating were made as described previously by Lim et al [4]. An WE43 In vivo evaluation of HA-WE43 nerve conduit…”
Section: Ha-coated Mg Disks Preparationmentioning
confidence: 99%